2014
DOI: 10.1007/s13313-014-0306-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the role of honey bees (Apis mellifera) as vectors of the bacterial plant pathogen Pseudomonas syringae

Abstract: Honey bees (Apis mellifera) have been implicated in the spread of the fire blight pathogen (Erwinia amylovora), and may transmit other bacterial plant pathogens in the process of pollinating crops. Furthermore, the movement of hives from one orchard to another could spread plant diseases over large distances. We investigated whether honey bees might play a role in the transmission of different pathovars of Pseudomonas syringae. We detected live P. syringae pv. actinidiae (Psa), a pathogen of kiwifruit (Actinid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Movement of honey bee hives may pose a potential pathway for the spread of myrtle rust against the prevailing wind direction and beyond its current distribution along the eastern seaboard and the North Territory of Australia. As noted by Pattemore et al (2014), little can be done to manage the transport of plant pathogens within the foraging range of a hive, but quarantine restrictions associated with movement of bee hives from currently infected to uninfected areas should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Movement of honey bee hives may pose a potential pathway for the spread of myrtle rust against the prevailing wind direction and beyond its current distribution along the eastern seaboard and the North Territory of Australia. As noted by Pattemore et al (2014), little can be done to manage the transport of plant pathogens within the foraging range of a hive, but quarantine restrictions associated with movement of bee hives from currently infected to uninfected areas should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of fungal spores administrated to the bees was based on the amount of colony forming units (CFU) of plant pathogens found on bees foraging on infected flowers, which commonly ranges from 10 3 to 10 6 CFU per bee (Dedej et al 2004;Pattemore et al 2014).…”
Section: Feeding Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytopathogenic bacteria have evolved to harness insects as vectors to affect their dissemination and delivery directly on or into their preferred plant hosts (Nadarasah and Stavrinides, 2011). The role of insects as vectors of phytopathogenic bacteria has been demonstrated in kiwifruit, P. syringae; grapevine, Xylella fastidiosa; corn, Pantoea stewartii; cucurbits, Serratia marcescens; cucurbits, Erwinia tracheiphila; pome, E. amylovora; citrus, Candidatus liberibacter, and potato, P. carotovorum pathosystems (Nadarasah and Stavrinides, 2011;Pattemore et al, 2014).…”
Section: Existence Of Biotic and Abiotic Associations That Lead To Comentioning
confidence: 99%
“…Most recent examples include citrus greening caused by bacteria of the genus 'Candidatus Liberibacter' that are transmitted by psyllids (Stokstad, 2012) and bacterial canker of kiwifruit and horse chestnut bleeding canker caused by the bacterium Pseudomonas syringae (reviewed by Lamichhane et al, 2014b). For kiwifruit canker, a large number of epidemiological studies on the disease suggested the role of latently infected propagation materials (Scortichini et al, 2012), insect vectors (Pattemore et al, 2014) or contaminated pollen (Gallelli et al, 2011;Stefani & Giovanardi, 2011). However, to the knowledge of the authors, no study has yet investigated the possible role of irrigation water as a source of pathogen inoculum.…”
Section: Introductionmentioning
confidence: 99%